Room-temperature carbon coating on MoS2/Graphene hybrids with carbon dioxide for enhanced sodium storage. (November 2019) - Feng, Meng; Zhang, Mengjie; Zhang, Huizhen; Liu, Xuehua; Feng, Hongbin
Abstract: Here we report an all-room-temperature approach to prepare carbon-coated MoS2 /graphene hybrids by combining the exfoliation of bulk MoS2 and simultaneously generation of amorphous carbon coverage using CO2 as carbon source. As the anode material for sodium ion battery, the carbon-coated MoS2 /graphene hybrids exhibit high rate capability (316 mA h g −1 at 2 A g −1 ) and superior cycling stability (415 mA h g −1 at 0.1 A g −1 after 150 cycles) than the uncoated one (180 mA h g −1 at 0.1 A g −1 after 150 cycles). The excellent electrochemical performance should be attributed to the synergistic combination of electrical conductivity of graphene and surface protection of carbon coating. This method is facile, efficient and believable to be widely used in making other 2D carbon-coated heterostructure materials with many functional applications. Graphical abstract: Image 1